ANALISIS KOMPARASI EFISIENSI BANK UMUM KONVENSIONAL (BUK) DAN BANK UMUM SYARIAH (BUS) DI INDONESIA - Margolang Irhas Muhammad; Widayatsari Any; Isbah Ufira (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to analyze the difference in efficiency values between Conventional Commercial Banks and Islamic Commercial Banks. Banking efficiency is measured by calculating the ratio between output and input. Input variables include total assets and third party funds, and output variables include financing and interest income. This study uses a non-parametric approach to calculate the number of inputs used by banks to produce different outputs using the Data Envelopment Analysis (DEA) method. The technical efficiency score using DEA is in the form of a percentage, if the efficiency value reaches 100% then the bank has achieved efficiency. To test the hypothesis in this study using the Independent Sample Test analysis. The samples used are Conventional Commercial Banks and Islamic Commercial Banks in the BUKU I-III category for the period 2015 to 2020. From the results of DEA analysis using DEA-CRS data processing in BUKU I and BUKU III, it is found that there are differences in efficiency values where Conventional Commercial Banks are more efficient. While in BUKU II there is no difference in efficiency values. Furthermore, from the analysis of hypothesis testing using SPSS 24.0 in the BUKU I-III category, it was found that there was an insignificant difference between the efficiency values of Conventional Commercial Banks and Islamic Commercial Banks.Keywords : analysis, Exchange rate, interest rates, financial, and stock price